2008
DOI: 10.1210/en.2008-0175
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Hyaluronidase Induces Ovarian Granulosa Cell Apoptosis and Is Involved in Follicular Atresia

Abstract: During ovarian folliculogenesis, the vast majority of follicles will undergo atresia by apoptosis, allowing a few dominant follicles to mature. Mammalian hyaluronidases comprise a family of six to seven enzymes sharing the same catalytic domain responsible for hyaluronan hydrolysis. Interestingly, some of these enzymes have been shown to induce apoptosis. In the ovary, expression of three hyaluronidases (Hyal-1, Hyal-2, and Hyal-3) has been documented. However, their precise cellular localization and role in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 66 publications
5
23
0
1
Order By: Relevance
“…In mouse granulosa cells, all three enzymes were capable of inducing cell apoptosis; however, the enzymatic activity of hyaluroglucosaminidase may not be relevant to the induction of apoptosis. Indeed, enzymatically inactive mutant HYAL1 induced the same level of apoptosis as the wild-type enzyme in cultured granulosa cells [47]. In the present study, the HA concentration in the pFFs was increased significantly at stage III.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In mouse granulosa cells, all three enzymes were capable of inducing cell apoptosis; however, the enzymatic activity of hyaluroglucosaminidase may not be relevant to the induction of apoptosis. Indeed, enzymatically inactive mutant HYAL1 induced the same level of apoptosis as the wild-type enzyme in cultured granulosa cells [47]. In the present study, the HA concentration in the pFFs was increased significantly at stage III.…”
Section: Discussionsupporting
confidence: 53%
“…It has recently been reported that the expression of hyaluroglucosaminidase (Hyal; Hyal1, Hyal2, and Hyal3) was correlated to increased granulosa cell apoptosis and follicular atresia in mouse ovaries [47]. In mouse granulosa cells, all three enzymes were capable of inducing cell apoptosis; however, the enzymatic activity of hyaluroglucosaminidase may not be relevant to the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the high molecular mass hyaluronan that occupies cell surface CD44 receptors maintains p-Akt and PI3K dependent signals that prevent cancer cell apoptosis, while hyaluronidase, and the oligosaccharides created by hyaluronidase, block these cell survival signals [36]. It has also been recently demonstrated that ectopic expression of all three different somatic hyaluronidases ( HYAL1, HYAL2 and HYAL3 ) induce granulosa cell apoptosis [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Dans l'ovaire, trois hyaluronidases (Hyal-1, Hyal-2 et Hyal-3) sont exprimé es. Leurs niveaux en ARNm sont significativement augmenté s dans les cellules apoptotiques de la granulosa et, donc, dans les follicules atré tiques de souris [21]. Or, les traitements de stimulation utilisé s en AMP affectent la concentration d'acide hyaluronique dans le liquide folliculaire humain [22].…”
Section: [ ( ) T D $ F I G ]unclassified